Gdansk Wound-QoL Questionnaire: Pilot Study on Health-Related Quality of Life of Patients With Chronic Ulcers With Emphasis on Professional Physician-Patient Relations - Marcela Nowak; Dorota Piechota; Wioletta Baranska-Rybak (Mattioli1885, 2024)
Introduction: Chronic wounds lower health-related quality of life, as they affect various aspects of life due to pain, odor, tedious treatment, and stigma from society. Implementing proper treatment, where patient is well informed and active is a key for best outcomes. Objective: The aim of the study was to evaluate health-related quality of life among the patients with chronic ulcers, with the use of new scale Gdansk Wound QoL. Methods: We enrolled 108 patients who met the inclusion criteria. Before the education on day 0 patients were asked to fill in Gdansk Wound-QoL questionnaire, that was developed in cooperation between dermatologists, general and plastic surgeons, as well as wound nurses, as well as fill the follow-up Gdansk Would-QoL on day 30, which was also the end of the study.  Results:  Study participants (n = 108) were on average 76.1 ± 10.8 years and all of whom had a venous ulcer on their lower limbs of average wound area of 10.8 cm2. Quality of life, according to the Gdansk Wound-QoL Questionnaire, increased on average by 36.7% after 30 days trial. Moreover, on the follow-up visit 94.4% of the patients stated that their knowledge on the disease has increased and everyone was satisfied with the course of treatment proposed by the current doctor. Furthermore, 44.4% of the study group increased their activity at the end of the study. Conclusion: This pilot descriptive observational study shows that Gdansk Wound-QoL questionnaire can provide professionals in wound care good feedback on health-related quality of life of patients with chronic wounds. This information has the potential to enhance patients' well-being and overall comfort"